PENYULUHAN PENGARUH MINUMAN BIKARBONAT TERHADAP KEBUGARAN FISIK SERTA PEMERIKSAAN ASAM URAT DAN TEKANAN DARAH DI TPA KAWATUNA KOTA PALU - Badaruddin, Rahma; Sulistiana, Ria; Ramadhan, Mohammad Zainul; Handayani, Fitriah; Akib, Muhammad Ihsan (Jurnal Abdimas Bina Bangsa, 2024)
Gouty arthritis is an inflammatory joint disease caused by increased uric acid levels in the blood due to impaired purine metabolism. This disease is increasing in prevalence throughout the world, including in developed countries such as the United States and developing countries such as China, Taiwan, and Indonesia. Sodium bicarbonate (NaHCO3) is one of the compound ingredients in beverage supplementation that is often consumed by the public. The function of sodium bicarbonate is able to accumulate extracellular acids including lactic acid. This is what gives the impact of reducing fatigue so that the body still feels fit The purpose of implementing this service program is to foster community knowledge in the Palu Kawatuna Landfill area about the effect of bicarbonate drinks on physical fitness, foster community knowledge about Gout Arthritis disease, conduct health checks in the form of checking blood pressure and uric acid levels to the community in the Palu Kawatuna Landfill Area. There were 6 participants with increased blood pressure or hypertension, and 6 participants showed high uric acid levels or hyperuricemia. Furthermore, the service team provided education and referral notes to a number of participants to check themselves to local health facilities for more complete examination and management.